Pelatihan Pembuatan Evaluasi Pembelajaran Berbasis Website Edukatif bagi Guru Madrasah Al-Jauharen Kota Jambi - Ely Surayya; Dewi Hasanah; Hindun Hindun; Ida Rianty; Rapiko Rapiko (Lembaga Pengembangan Kinerja Dosen, 2025)
This community service program aims to improve teachers' competency in creating educational website-based learning evaluations using the Kahoot and Quizizz applications. The implementation method of this community service uses online and offline training with presentations and tutorials. The training was attended by 30 teachers from MI, MTs, and MA at the Al-Jauharen Islamic Boarding School in Jambi City. The evaluation instrument for this community service program used pre-test and post-test questionnaires which were then analyzed using percentage tests. The results of this community service activity indicate that there is an increase in the understanding of Al-Jauharen Madrasah teachers in Jambi City regarding creating educational website-based learning evaluations using the Kahoot and Quizizz applications. In addition, teachers are able to create learning evaluations using Kahoot and Quizizz for the subjects they teach.